A note on the second order of accuracy di˙erence scheme for elliptic-parabolic equations in H¨older spaces - Ashyralyev, A.; Gercek, O.; Zusi, E. (Ye.A.Buketov Karaganda State University Publ., 2018)
The present paper is devoted to the study of a second order of accuracy di˙erence scheme for a solution of the elliptic-parabolic equation with nonlocal boundary condition. The well-posedness of the second order of accuracy di˙erence scheme in H¨older spaces is established. Coercivity estimates in H¨older norms for an approximate solution of a nonlocal boundary value problem for elliptic-parabolic di˙erential equation are obtained. Results of numerical experiments are presented in order to support the aforementioned theoretical statements.
Гёльдер кеңістіктеріндегі эллипстік-параболалық түрдегі теңдеулер үшін дәлдігі екінші ретті айырымдық схемалар жөнінде ескертпе
Замечание о разностной схеме второго порядка точности для эллиптико-параболических уравнений в пространствах Гёльдера
Keywords: di˙erence scheme; elliptic-parabolic equation; H¨older spaces; well-posedness; coercivity inequa-lities